2014
DOI: 10.1308/003588414x13946184900480
|View full text |Cite
|
Sign up to set email alerts
|

Day-case minimally invasive excision of a giant mediastinal parathyroid adenoma

Abstract: Inferior parathyroid adenomas in the mediastinum can be a troublesome cause for hypercalcaemia, requiring a full collar incision or, occasionally, a sternotomy. We report a case of a giant parathyroid adenoma in a 61-year-old woman on warfarin, which we excised via a minimally invasive transcervical approach after radiological localisation. The procedure was performed as a day case and, at six weeks, the patient had recovered fully with biochemical resolution of hypercalcaemia. This case demonstrates that focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 3 publications
0
15
0
1
Order By: Relevance
“…Surgical excision of the hyper functioning gland is the treatment of choice for parathyroid adenomas. [ 13 ] The surgical approach for an inferior giant parathyroid adenomas extending on to the mediastinum can be cumbersome requiring a full collar incision or occasionally a median sternotomy. Our case further demonstrates that a focused trans-cervical excision of giant inferior parathyroid adenoma is a viable approach for resection and should be considered prior to a formal neck exploration or sternotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical excision of the hyper functioning gland is the treatment of choice for parathyroid adenomas. [ 13 ] The surgical approach for an inferior giant parathyroid adenomas extending on to the mediastinum can be cumbersome requiring a full collar incision or occasionally a median sternotomy. Our case further demonstrates that a focused trans-cervical excision of giant inferior parathyroid adenoma is a viable approach for resection and should be considered prior to a formal neck exploration or sternotomy.…”
Section: Discussionmentioning
confidence: 99%
“…10 Median sternotomy and thoracotomy are of great interest in cases of large inaccessible masses. 11 Our case showed that a trans-cervical excision of giant parathyroid adenoma is a viable approach for resection and should be considered prior to more aggressive approachs.…”
Section: Discussionmentioning
confidence: 77%
“…There is a documented procedure of excision of even giant parathyroid adenoma using minimally invasive transcervical approach after its radiological localisation pre-operatively resulting in full recovery. This case leads to the conclusion that this method is an advantageous alternative for neck exploration or sternotomy [44].…”
Section: Minimally Invasive Parathyroidectomy and Minimally Invasive Radio-guided Parathyroidectomymentioning
confidence: 75%